PENGENDALIAN SEL BIOFILM BAKTERI PATOGEN OPORTUNISTIK DENGAN PANAS DAN KLORIN - Yusnita Wahyuni Silitonga; It Jamilah; Dwi Suryanto (Saintia Biologi, 2012)
Opportunistic pathogenic bacteria are bacteria that are naturally not present in an environment that, but it dues to contamination of the environment by human waste. From previous research it was found E. coli, Staphylococcus sp. and Salmonella were opportunistic pathogens of the shrimp aquaculture (Percut, Pantai Labu, Pantai Cermin). The aims of this study is to know the ability of these bacteria to form biofilms as well as its control using chlorine and heat. In order to test the ability of the bacteria to form biofilms, the stainless steel have been soaked in SWC media for 1, 3, 6 days. E. coli, Salmonella, and Staphylococcus sp. may form biofilms on incubation of the 1st day but the highest growth was on the 6th day of incubation by E. coli with a 6,35 x 104 CFU/SS, whereas of the lowest biofilm number was found in Salmonella with a 0,28 x 104 CFU/SS. The number of biofilm cells grow in line with a length of incubation. In this research, the most effective concentration of chlorine to kill biofilm cell was 225 ppm for 2 minutes and heat was 100 0C for 5 minutes. The higher the concentration of chlorine and the temperature given more effective to kill the bacteria. Keyword: biofilm, chlorine, heat, opportunistic, stainless steel